Lightlike Hypersurfaces of Meta-Golden Semi-Riemannian Manifolds - Feyza Esra Erdoğan; Selcen Yüksel Perktaş; Şerife Nur Bozdağ; Bilal Eftal Acet (Mathematics, 2023)
In this research, we embark on the examination of lightlike hypersurfaces within an almost meta-Golden semi-Riemannian manifold. We investigate the properties of the induced structure on a lightlike hypersurface by meta-Golden semi-Riemannian structure. Then, we introduce invariant lightlike hypersurfaces, anti-invariant lightlike hypersurfaces and screen semi-invariant lightlike hypersurfaces of almost meta-Golden semi-Riemannian manifolds and give examples.